ANALYSIS OF OBTAINING AN IMAGE WITH THE TOMOGRAPH - KRYVENCHUK, YURII; NEVINSKYI, DENYS; NOVYTSKYI, YURII; VYKLYUK, YAROSLAV (Herald of Khmelnytskyi National University. Technical sciences, 2022)
CT scans vary from manufacturer to manufacturer. There are several generations of CT. The concept of CT generation is not so much related to the time of its birth, but to the use in the scanner of the type of motion of the emitter-detector system. The generation number (first, second, third, fourth, etc.) is related to the type of tube-detector system design. Three types of scanners are now available: third, fourth and fifth generation. The life of the first generation of CT was fleeting: the duration of the scan did not suit - about 20 minutes. and the computer reconstruction of the image took too long. Only the brain could be examined on such devices. As for the human body, the image turned out blurry, blurred. But the process of improvement continues. Today, research is being conducted on fourth- and fifth-generation devices. They have not one, but many X-ray emitters, up to 200. It uses a very powerful processor with high-speed information processing - up to 10 million operations per second. As a result, the scan time was reduced to 40-50 milliseconds. It is now possible (here is a scientific idea!) To see on the telemonitor the reduction of certain transverse layers of the heart 1-2 millimeters thick. At spiral CT in the course of research with simultaneous constant rotation of system "tube - detectors" the table constantly moves and thus there is a spiral movement of a fan-shaped beam through a patient's body. Spiral CT makes it possible to examine the anatomical region in one period of respiratory arrest, and the thickness of the reconstructed layer is not related to the original width of the tomogram. Obtaining thin conjunctival sections, which are tightly arranged in a spiral, allows you to get three-dimensional reconstructions. In combination with intravenous bolus contrast and subtraction data processing, CT angiograms can be obtained, which reproduce images of large vessels. In recent years, multispiral (multislice) CT has been used, which is based on the principles of imaging as in spiral CT, but due to multi-row detectors for full rotation of the system "tube detectors" can display more than one slice (currently from 2 to 16 images). This has made it possible to perform studies of the heart, study a large anatomical area, such as the lungs, thin sections in one breath hold, and significantly improve the quality of multiplanar and three-dimensional reconstructions. In electron beam tomography, the source of X-rays is a large electron gun with several massive parallel anode targets located in semiconductor rings around the patient. The intense anode beam is directed along the tungsten anode rings. The electron beam thus obtained passes through the patient's body and is received by a fixed array of detectors. This achieves a high tomography rate, which is sufficient for the study of a moving heart: clearly delineated images can be obtained without the use of synchronization with the ECG. With the help of electron-beam tomography it is also possible to perform CT angiography and construction of high-quality three-dimensional reconstructions. Thus, modern medicine is impossible without CT. For example, in neurology, computed tomography, in addition to skull bones, well identifies the ventricles of the brain, venous sinuses, subarachnoid cisterns, interhemispheric fissure, cortex, basal nodes, inner capsule, trunk, cerebellum and other structures. The radiation load does not exceed the level usual for X-ray examination. At the same time, CT scans provide 100 times more information about the brain than conventional skull x-rays. But its importance is not limited to use only for the diagnosis of various diseases. Under the control of CT perform punctures and directed biopsy of various organs and pathological foci. The role of CT in the control of conservative and surgical treatment of patients is extremely important. CT is a valuable method of accurate localization of tumors and directing the radiation source to the focus when planning radiation treatment of malignant tumors.
Keywords: tomogram; thin slice; image reconstruction